ECONOMIC EFFICIENCY CALCULATION PROCEDURE FOR THE AUTOMATIC WATER-LEVEL REGULATING INVARIANT SYSTEM IN THE BOILER SHELL - A. N. Kuchorenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
The three-element system for automatic water-level regulation in the boiler shell as well as its modifications received maximal dissimilation in the Republic of Belarus and the CIS countries power economies. Though, they possess the following shortages: occurrence of the steadystate errors at the end of the transient process during the control response to internal disturbances and those by over-heated steam; large level deviations at sharp and significant load changes, which often leads to the boiler or the power block deloading or stoppage. As a remedial action against the mentioned disadvantages, the invariant systems for the drum boiler automatic feed regulation were developed earlier. The first variant of the automatic regulation invariant system with the equivalent external disturbance individualization differs from the typical one in the way that they select the stabilizing controller arrangement on the basis of transmission response of the optimal controller. And the compensating device dynamic settings structure and parameters are chosen with respect to the equivalent controlled member including the stabilizing controller inner contour. The second variant offers the compensating device transmission response to the equivalent external disturbance represented as series-connected typical sections: a real differentiator and a quick-response unit. For the control action maximum value reducing in this scheme, there is a suppressing device additionally installed at the exit of the equivalent external disturbance compensation device. The automatic regulation invariant systems eliminate steady-state errors at all impacts and allow improving significantly the level control quality at variable conditions. For economic efficiency evaluation of the boiler-shell water level automatic regulation innovative system implementation as a system, the author proposes a technique allowing calculating the main components of the economic effect of its implementation. Inter alia, increasing reliability (faultlessness) of the boiler operation, increment in the boiler efficiency at the expense of essential action-execution time decrease as compared with the typical automatic regulation system and longevity of its operation.